Implementasi Kebijakan Pengelolaan Pariwisata pada Situs Citaman Kab. Pandeglang, Banten - Nengsih, Yusti; Stiawati, Titi (Epistemik Press, 2025)
This study examines the implementation of cultural tourism policies at the Citaman Site, located in Pulosari District, Pandeglang Regency, Banten Province. The research addresses several key issues, including the limited dissemination of information regarding the site's tourism development, insufficient infrastructure and facilities, and a lack of active involvement from the Pandeglang Regency Tourism and Culture Office in terms of management, oversight, and maintenance. Additionally, there has been no formal assignment requiring the site's custodian to report on tourism development progress. The research applies George C. Edward III’s policy implementation theory, which includes four main indicators: communication, resources, disposition, and bureaucratic structure. Using a descriptive method with a qualitative approach, the findings reveal that the implementation of the cultural tourism policy at the Citaman Site has been ineffective. This is due to the inadequate outreach by the Tourism and Culture Office, poor facility development, limited oversight and maintenance efforts, and the absence of formal reporting duties assigned to the site's custodian.